Identification of the gene(s) coding for the trans-sialidase of Trypanosoma cruzi. - Parodi, A J (EMBO J, 1992)
The gene(s) encoding the Trypanosoma cruzi shed-acute-phase-antigen (SAPA) has a 5' end encoding a region containing two totally and two partially conserved Ser-X-Asp-X-Gly-X-Thr-Trp motifs which are present in bacterial neuraminidases, and a 3' end encoding tandemly repeated units of 12 amino acids. It is now reported that 54-87% of the total neuraminidase activity present in the parasite could be immunoprecipitated with polyclonal or monoclonal antibodies against the repeated amino acid units of SAPA. These immunoprecipitates also had greater than 80% of the trans-sialidase activity of the parasite. SAPA used sialyllactose, fetuin and 4-methylumbelliferyl-sialic acid as substrate donors. In the presence of a suitable acceptor molecule (lactose) the sialic acid residues were transferred to the disaccharide, whereas in the absence of acceptors the residues were transferred to water. If relatively inefficient acceptors (maltose or cellobiose) were added to the incubation mixtures, the sialic acid units were transferred both to the disaccharides and to water. It is concluded that a major T. cruzi antigen has both the trans-sialidase and the neuraminidase activities of the parasite. Both activities are probably located on the N-terminus of SAPA since antibodies directed against the C-terminus, which contains the repeated amino acid units, do not affect the enzymatic activities. IMAGES: